The Different Roles of Cobalt and Manganese in Metal‐Organic Frameworks for Supercapacitors. Issue 3 (8th February 2021) - Iqbal, Rashid; Sultan, Muhammad Qaisar; Hussain, Sabir; Hamza, Mathar; Tariq, Ayesha; Akbar, Muhammad Bilal; Ma, Yingjie; Zhi, Linjie
Abstract: Conductive metal‐organic frameworks (MOFs) are promising electrode materials for supercapacitors (SCs) because of their tunable structures, high specific surface areas, and superior conductivity. However, it remains challenging to develop conductive MOFs for organic SCs and the role of metal ions in the electrochemical performance of MOFs is still unclear but is shown to be a key factor in determining MOFs performance. Herein, two high‐performance ultra‐thin redox conductive 2D MOFs (>6000 S m −1 ) for SCs are prepared, and the effects of metal ions on the capacitive performance of MOF electrodes are investigated. Co 2+ and Mn 2+ with the same ligand provide two MOFs featuring almost the same structures and specific surface areas but show great differences in electrochemical performance except that both MOFs exhibit outstanding electrochemical performance and good cycling stability with a capacity retention of >85% after 10 000 cycles. Different metal ions endow the two MOFs with different redox behaviors, conductivities, and energy levels, where Co‐MOF shows superior specific capacity compared to Mn‐MOF. This work expands the possibility of the use of MOFs in SCs and gives insight into the roles of metal ions in MOFs. Abstract : Two high‐performance ultra‐thin conductive 2D metal‐organic frameworks (MOFs) for organic supercapacitors (SCs) are developed and the effects of metal ions on the capacitive performance of MOF electrodes are investigated. Different metal ions endow both MOFs with almost the same structures and specific surface areas but different electrical conductivities, redox behaviors, and band gaps, thus resulting in different electrochemical performances in SCs.